Stratigraphic architecture of alluvial terraces in the Yunganza river - Romero, Cristian (2020)
The study of fluvial sedimentation patterns (FSP) allow us to analyze tectonic and climatic behavior in a specific region, and, understand how rivers modify the relief. FSP can be studied from the analysis of the stratigraphic record of their deposits. In the northern Andes, FSP interact with erosion rates and detritus available for sedimentation rates. In the south of the sub-Andean zone, the Yunganza river basin corresponds to a confined fluvial basin and feeder of the Santiago river, and offers the opportunity to study this region FSP. The aim of this research is to present the stratigraphic record analysis of: ancient alluvial terraces (TA-1 and TA-2) and alluvial deposits (DA) in the Yunganza river basin, in the vicinity of El Rosario in order to define PSF. Our research is supported by documentation of the lithological record, sedimentary structures, stratigraphic architecture, thickness and paleo-currents measurement. Seven facies are described: LT-1 and LT-2 describe conglomerates associated with distal debris flows, whilst, LT-3 describes conglomerates and breccias associated with proximal debris flows. LT-4, and LT-5, and LT-6 describe sandstones genetically linked to bars and fluvial channel macro-forms, last, LT-7 describes siltstones associated with flood plains. Paleocurrent data indicate that: TA-1 presents flow direction to NE-E, whereas, TA-2 indicates a sediment transport direction to N. The TA-1 modal composition indicates a detrital provenance of a sedimentary block rich in quarts, while the TA-2 modal composition indicates a recycling period of TA-1. The thickness measurement in TA-1 and TA-2 indicates an intensely erosive period in TA-1. Finally, fluvial sedimentation patterns in the Yunganza river are genetically linked to periods of exhumation on the west side of the river.